MECHANICAL PERFORMANCE OF NYLON FIBER-BASED FIBER CONCRETE WITH ARTIFICIAL COARSE AGGREGATE FROM TANGKILING CLAY - Liliana Sahay; Abertun Sagit Sahay; Supiyan; Syahrozi; Giris Ngini; Theo Fransisco (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2026)
This study investigates the physical properties of artificial coarse aggregate produced from Tangkiling clay and examines the influence of nylon fiber addition on the bulk density, compressive strength, and flexural strength of fiber-reinforced concrete. The aggregate was manufactured by firing clay at 1000°C for 15 minutes. Results indicate that the produced aggregate does not qualify as lightweight aggregate under SNI 03-2461-2002, with a maximum bulk density of 984 kg/m³, exceeding the 880 kg/m³ limit. The fiber-reinforced concrete exhibited bulk densities between 1,830 and 1,855 kg/m³. Incorporating 0.4% nylon fiber increased the bulk density above 1,850 kg/m³, classifying the mix as normal-weight concrete. Mixes containing 0.20–0.40% nylon fiber met the structural lightweight concrete requirement with compressive strengths exceeding 17.24 MPa, while 0.36% fiber content achieved the highest compressive strength of 20.03 MPa. Flexural strength ranged from 2.40 to 2.80 MPa, surpassing the 2.3 MPa minimum set by SNI 2461-2014, with the optimal value of 2.79 MPa recorded at 0.23% fiber content.